The Hepatoprotective and Antioxidant Benefits of Timely Dietary Supplementation with Green Tea Powder in Awassi Sheep - Salam Ketab Rebat (American Journal of Biomedicine and Pharmacy, 2026)
The aim of this investigation was to evaluate, over time, the effect of dietary supplementation with green tea (Camellia sinensis) powder on liver protection and antioxidant activity in Awassi sheep. The 12 clinically healthy adult Awassi sheep (3–4 years old) were randomly assigned to 3 groups of 4 sheep each. For 30 days, a standard feed was supplied to the control group (G1) and a standard feed supplemented with green tea powder at a rate of 150 g/10 kg of feed (G2) and 250 g/10 kg of feed (G3) respectively. On day 0, day 15 and day 30, blood samples were obtained from the same animals to determine the levels of serum liver enzymes (ALT, AST, ALP), markers of oxidative stress (MDA) and antioxidant capacity (GSH, TAC). All groups had similar baseline values at day 0. Early improvements were mainly seen in ALP, MDA and GSH levels by day 15 particularly in the higher dose group. The supplementation with green tea led to significant dose-dependent improvements by day 30 with decreased concentrations of ALT, AST, ALP and MDA and increased concentrations of GSH and TAC. The present results showed that treatment with green tea powder may improve the biochemical stability of the liver and strengthen the antioxidant defence mechanisms in Awassi sheep, depending on the dose and duration. Article title: Effect of green tea powder on the activities of liver enzymes in Awassi sheep.Article.